Efeitos do extrato aquoso obtido das folhas da Hyptis pectinata (sambacaitá) sobre o sistema nervoso central de roedores - Bueno, Alexsandro Xavier (2005)
In this work we studied the effects of the aqueous extract (AE) from the Hyptis pectinata leaves on rodents (mice and rats)central nervous system. The following experimental models were used to have access to possible central effects of the extract: pharmacological screening, open field, forced swimming, apomorphine-induced hypothermia, elevated plus maze and tiopental-induced sleepig durantion. In the pharmacological screening test the only noticeble effect of the AE (400 mg/Kg) was a decrease in the frequency of grooming behavior. In the open field test the AE decreased the time rats spent grooming (AE400: 51.3 ± 8.8, q= 5.513, p<0.01), an effect similar to diazepam (con: 107.3 ± 14.2; diaz: 15.4 ± 4.3, q= 9.049, p<0.001). In the forced swimming test the AE (400 mg/Kg) decreased the immobility time of mice when compared with control (con: control: 181.3 ± 7.2 s; imip: 91.6 ± 8.9 s, q= 7.958, p<0.001; AE400: 111.6 ± 14.5 s, q= 6.193, p<0.001), indicating a possible antideprerssive effect. This effect was confirmed in the apomorphine-induced hypothermia model where the extract (200 mg/Kg) antagonized the decrease in rectal temperature caused by apomorphine (AE200: -0.27o C, q= 5.588, P<0.001), an effect similar to imipramine (5 mg/Kg), a classical tryciclic antidepressant (control: -1.08o C; imip: 0.02o C, q= 7.589, p<0.001). No effect of the AE was detected in the elevated plus maze and in the tiopental-induced sleeping time models. Our results suggest a possible antidepressive effect of the aqueous extract obtained from the leaves of Hyptis pectinata.